From budgets to growth: a global perspective on the influence of the government on economic growth - Lum, Shau En (Nanyang Technological University, 2024)
This paper investigates the dynamic relationship between government spending and economic growth, focusing on the post-Global Financial Crisis (GFC) era as public debt levels rose significantly after the crisis. Expanding on Khan and Kumar's (1993) augmented Solow model that distinguished the roles between public and private capital investment, we incorporated the public sector's size and analyzed data from a broader sample of countries spanning 1995-2019 using an Ordinary Least Squares (OLS) model.